Taking community-based system to Malaysian communities for disaster management - Ajayi, Binyamin; Badi, Bakhtiyar; Al-ani, Mustafa; Ahmad Dahlan, Abdul Rahman (Centre for Promoting Ideas, USA, 2011)
This study explores the efforts, Malaysia, is putting in place, using the pervasiveness of ICT in managing disasters; both naturally and man-made. These efforts had given birth to various agencies and initiatives from prediction/mitigation to control and management but yet the loss of lives and properties during such incidents, which are bound to happen, has been a call for concern. In fact records of such disasters kept growing when one curiously views recent flooding in Malaysia. A collaborative system initiative is expected to co-exist within the government agencies on disaster management where expertise, resources and information sharing will be enabled on a real time basis. The community through the institution of the mosque was brought on board into such system as they are seen to be the closest to the populace. These steps will no doubt make the perpetual efforts of government agencies to yield the required results. We thus opined that training these communities, which is expected to institute a comity of volunteers, in the science of how to gather information and make good use of same in the event of the disaster occurrence will go a long way in making the tax payer money worthwhile.